Relevansi Pengampunan Korupsi dalam Perspektif Islam Dengan Hukum yang Berlaku - Muhammad Farid Zulkarnain; Hilalludin Hilalludin; Fida Said As Suny (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Corruption remains a pervasive issue in Indonesia, spanning across all levels of governance from national to local, impacting both public and private sectors. Rooted deeply within societal and governmental structures, corruption undermines ethical standards, economic stability, and public trust. This research aims to examine the implications of granting pardons to corruption offenders within Indonesia's legal framework. The study employs a literature review methodology, synthesizing insights from various scholarly sources. Findings suggest that pardons, whether through remission or sentence reduction, are intended to expedite case resolutions, facilitate asset recovery, and promote social reintegration of offenders. However, the practice of pardoning corruption offenders raises ethical and legal dilemmas concerning justice for victims and societal repercussions. From an Islamic perspective, corruption is unequivocally condemned, emphasizing principles of justice and restitution. Islamic jurisprudence allows for forgiveness only upon sincere repentance and restitution of unlawfully acquired assets. Indonesian legal policies rigorously regulate the conditions under which pardons are granted, including requirements such as fine payments and cooperation with law enforcement. Thus, the process of granting pardons demands careful consideration to uphold justice, ensure societal trust, and maintain deterrence against future corrupt practices.